High-Resolution Speckle Imaging at Gemini-North: Exoplanets and Beyond - Howell, Steve B.; Horch, E.; Everett, M. E.; Ciardi, D. (2013)
Using our state-of-the-art 2-channel speckle imaging instrument, we have recently obtained diffraction-limited optical images at the 8-m Gemini-N telescope. The primary science goal was to search for faint (delta_mag = 4-6 mag) and nearby (<0.05") stellar companions around potential planet hosting stars as part of the small small exoplanet validation for the NASA Kepler and ESA CoRoT missions. As a demonstration of the instrument capabilities on Gemini, we achieved an angular resolution of ~20 mas which yielded the highest resolution ground-based optical image of the Pluto-Charon system ever obtained. Our instrument is likely to return to Gemini-N in mid-2013 for observations by general community programs
Conference Name: American Astronomical Society Meeting Abstracts #221 ADS Bibcode: 2013AAS...22114208H
Keywords: dept.phy

The Relation Between Radius, Mass, and Incident Flux of Exoplanets - Weiss, Lauren M.; Marcy, G. W.; Rowe, J.; Isaacson, H. T.; Howard, A.; Fortney, J. J.; Miller, N.; Demory, B.; Fischer, D.; Adams, E. A.; Dupree, A. K.; Howell, S. B.; et al. (2013)
We measure the mass of a modestly irradiated giant or "warm Jupiter," KOI-94d, in order to calculate its density. We wish to determine whether this planet, which is in a 22 day orbit and receives 107 times as much incident flux as the Earth, is bloated like "hot Jupiters" or as dense as our own Jupiter. In addition to its warm Jupiter, KOI-94 hosts at least 3 smaller planets, all of which were detected through transits by the Kepler Mission. This presents the opportunity to characterize a multi-planet system and to test dynamic stability and formation theory through observations of the masses and orbital elements of these planets. With 26 radial velocity measurements of KOI-94 from the W. M. Keck Observatory/HIRES, we measure the mass of the giant planet and upper limits to the masses of the three smaller planets. Transit timing variations will allow us to hone the mass measurements of the three smaller planets. Using the KOI-94 system and all other planets with published values for both mass and radius, we establish two fundamental planes for exoplanets that relate their mass, incident flux, and radius from a few Earth masses up to ten Jupiter masses: log(Rp/RE) = 0.007 + 0.53 log(M/ME) - 0.001 log(F/[erg/s/cm2]) for Mp < 150ME; log(Rp/RE) = 0.67 - 0.036 log(M/ME) + 0.06 log(F/[erg/s/cm2]) for Mp > 150ME. We also solve these planes in density-mass-flux space: log(ρp/[g/cm3]) = 0.69 - 0.57 log(M/ME) + 0.02 log(F/[erg/s/cm2]) for Mp < 150ME; log(ρp/[g/cm3]) = -1.23 + 1.10 log(M/ME) - 0.18 log(F/[erg/s/cm2]) for Mp > 150ME.
Conference Name: American Astronomical Society Meeting Abstracts #221 ADS Bibcode: 2013AAS...22140705W
Keywords: dept.phy

Exoplanet Characterization by Proxy for Kepler-61b: How a Nearby Star Bumped a Planet Out of the Habitable Zone - Ballard, Sarah; Charbonneau, D.; Fressin, F.; Torres, G.; Irwin, J.; Desert, J.; Ciardi, D.; Crepp, J. R.; Henze, C.; Bryson, S.; Howell, S. B.; Horch, E.; et al. (2013)
We present the validation and characterization of Kepler-61b: a 2.5 R_Earth planet orbiting near the inner edge of the habitable zone of a low-mass star. Our characterization of the host star Kepler-61 is based upon our identification of a spectroscopically similar star located 4.9 pc from Earth. This proxy star to Kepler-61 has a published direct interferometric radius and effective temperature measurement, which we apply in tandem with the Kepler photometry to characterize the planet Kepler-61b. The technique of identifying a nearby proxy star with directly measured properties allows for an independent check on stellar characterization via the traditional measurements with stellar spectra and evolutionary models. In this case, such a check had profound implications for the putative habitability of Kepler-61b. This work was performed in part under contract with the California Institute of Technology (Caltech) funded by NASA through the Sagan Fellowship Program
Conference Name: American Astronomical Society Meeting Abstracts #221 ADS Bibcode: 2013AAS...22140707B
Keywords: dept.phy